Book Reviews. (1st April 2018) - Schifferstein, Hendrik N. J.; Parham, Susan; Carta, Silvio; Parasecoli, Fabio
Katja Gruijters Food Design: Exploring the Future of Food, Ed van Hinte (2016)Houten, the Netherlands: Uitgeverij Terra, 216 pp., ISBN: 9789089896889, p/bk, €40Food and Architecture: At the Table, Samantha L. Martin-McAuliffe (ed.) (2016)London and New York: Bloomsbury Academic, 304 pp., ISBN: 9780857857347, p/bk, 24.99Food Democracy: Critical Lessons in Food, Communication, Design and Art, Oliver Vodeb (ed.) (2017)Bristol: Intellect, 500 pp., ISBN: 9781783207961, p/bk, 30